Self-Efficacy as a predictor of entrepreneurial interest among university students: A quantitative study - Mulyani, Yusni; Arbi, Yaumal (Universitas Negeri Padang, 2025)
Entrepreneurship is increasingly seen as an important strategy in reducing unemployment among college graduates and promoting economic resilience. This study aims to examine the predictive role of self-efficacy an individual's belief in their ability to complete a specific task in shaping entrepreneurial interest among university students. Self-efficacy is believed to influence how individuals perceive opportunities and challenges in starting a business, thereby playing a central role in entrepreneurial motivation. A descriptive quantitative approach was used in this study, with data collected through a structured questionnaire distributed to 348 students from nine faculties at the University of Padang. The questionnaire was designed using a Likert scale to measure levels of self-efficacy and interest in entrepreneurship. Data analysis was conducted using descriptive tests, normality, linearity, homogeneity, and hypothesis testing using Pearson's correlation. The results of the study showed a positive and significant relationship between self-efficacy and entrepreneurial interest (significance value= 0.012), with a Pearson correlation coefficient of 0.113, indicating a moderate relationship. Most students demonstrated relatively low levels of self-efficacy and interest in entrepreneurship, but students with high self-efficacy tended to have greater interest in entrepreneurship. These findings emphasize the importance of integrating self-confidence building into university entrepreneurship programs to enhance students' readiness and motivation to enter the entrepreneurial world after graduation.